SIMULASI DINAMIKA MOLEKULER PERMEABILITAS CH4 DAN CO2 PADA MEMBRAN ANORGANIK - Martiana, Reni (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
Permeability of CH4 and CO2 through inorganic membrane was investigated using Molecular Dynamics simulations at canonical ensemble. The results show that the potential of CH4 and CO2 separation caused by the effect of molecular orientation on the basis of molecular sieving was observed on membranes with a pore diameter of 0.5 nm and 0.842 nm thickness. Keywords: gas permeability, inorganic membrane, molecular sieving, molecular dynamics